Physical Match - Naiman, Aaron E.; Farber, Eliav; Stein, Yossi (Informatica, 2019)
We present an approach to solving the problem of “physical match,” i.e., reconnecting back together broken or ripped pieces of material. Our method involves correlating the jagged edges of the pieces, using a modified version of the longest common subsequence algorithm.